2016
DOI: 10.1128/aem.02382-15
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Polyvalent Bacteriophages by Sequential Multiple-Host Approaches

Abstract: Many studies on phage biology are based on isolation methods that may inadvertently select for narrow-host-range phages. Consequently, broad-host-range phages, whose ecological significance is largely unexplored, are consistently overlooked. To enhance research on such polyvalent phages, we developed two sequential multihost isolation methods and tested both culturedependent and culture-independent phage libraries for broad infectivity. Lytic phages isolated from activated sludge were capable of interspecies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
134
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(137 citation statements)
references
References 30 publications
3
134
0
Order By: Relevance
“…Other studies have shown that sequential or simultaneous addition of multiple hosts should be used to isolate phages with broader host range. However with these methods the host range of these phages seems limited to the bacterial species used during their isolation1646. The current study indicates that it is possible to isolate such phages using a single host.…”
Section: Discussionmentioning
confidence: 77%
“…Other studies have shown that sequential or simultaneous addition of multiple hosts should be used to isolate phages with broader host range. However with these methods the host range of these phages seems limited to the bacterial species used during their isolation1646. The current study indicates that it is possible to isolate such phages using a single host.…”
Section: Discussionmentioning
confidence: 77%
“…However, the latter strategy requires prior knowledge of related genetic elements with the desired host-range and the capacity to engineer those elements into a functional phage, which often results in laborious ad hoc trial and error periods (Ando et al, 2015; Chen et al, 2017; Gebhart et al, 2017; Hawkins et al, 2008; Heilpern and Waldor, 2003; Lin et al, 2012; Nguyen et al, 2012; Scholl et al, 2009; Yoichi et al, 2005). Harnessing natural evolution, on the other hand, requires elaborate co-culture and selection strategies that balance the need to have the phage population grow and mutate while also providing an alternative host for phage mutants to reproduce on (Qimron et al, 2006; Ross et al, 2016; Yu et al, 2015). A recent paper by Yosef and colleagues combined the approaches of rational host-range engineering with evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the disparate location of these EAEC isolates, and that PDX formed plaques on caseassociated EPEC strains from children in the Seattle area, the results suggested that the sequential method (21) for isolating phage that recognized more core bacterial antigens was successful.…”
Section: Discussionmentioning
confidence: 99%
“…Phage were sequentially isolated from E.coli strain MC4100, EPEC strain LRT9, and EAEC clinical isolate EN1E-0227 using a sequential isolation technique to enrich for core antigen recognition (21). Several clearly defined plaques from the final overlay were picked using a sterile inoculating needle and suspended in microcentrifuge tubes containing SM buffer.…”
Section: Methodsmentioning
confidence: 99%